Tropical montane cloudforest - Kenneth J Feeley (Frontiers of Biogeography)
cover: Inside a tropical montane cloudforest near timberline in the southern Peruvian Andes of Manu National Park (13.12345 S, 71.61721 W, 3600 m.a.s.l.). Picture by Kenneth Feeley.